Demographic and Laboratory Parameters among Covid-19 Outpatients Versus and Hospitalized Patients - Ghuroob Dalil Dhumad, Haider Sabah Kadhim, Haider Ahmad Shamran, Hatem Dheyab Abed (Pakistan Journal of Medical & Health Sciences, 2022)
The present study addresses the impact of age and gender on poor diagnosis COVID-19 disease and monitoring the levels of the serum biomarkers: LDH, D-dimer, CRP, TGF-B, IL-6 among COVID-19 patients. The study included 100 COVID-19 patients, recruited from hospitals in Baghdad governorate from February 2020 to May 2020 of both genders with media range of age of 38-59 years. Data revealed no significant impact of gender on COVID-19 disease outcome. Whilst age of participants was significantly higher (P<0.001) in needed ICU/admission died patients(59.0±12.67 years) compared to that of well -discharged patients (38.83±11.74 years). Age had a positive significant correlation with D-dimer (r= 0.276, p= 0.006), LDH (r= 0.318, p= 0.003), ferritin (r= 0.307, p= 0.005), CRP (r= 0.470 p<0.001), and WBC count (r= 0.410, p<0.001). D-dimer, LDH, ferrtin, and CRP levels were significantly higher (P<0.001) in needed ICU/admission died patients ‘group compared to those recorded in well-discharged patients’ group.The sensitivity and specificity of the tests at P<0.001 at cut off value of D-dimer= 0.56mg/ml, 285.7 U/L, 387.97 ng/ml, and 36.3 mg/Lwere (81 and 94%), (71 and 76%), (86 and 84%), and (91 and 84%), for D-dimer, LDH, ferritin, and CRP, respectively.